Creative Writing Skills - Dr Mohd Shafi Dar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Language is no doubt considered as one of the most substantial elements of education and literacy. In India productive skills of language are given significance of which writing is the most preferred one. It is suggested that teachers must in some way make writing a part of the learner‟s world. Creative writing includes writing and getting it published. The purpose of this paper is to make students, researchers and teachers aware of the simple rules that they must learn to have competence in writing creatively.